Perceived barriers, knowledge and reported practices of infection prevention and control among clinical nursing and medical students of a Nigerian University - Akinwaare, Margaret Omowaleola; Bello, Khadijat Oyinade; Ani, Odinaka (International Journal of Infection Control, 2020)
Infection control is a very important aspect of teaching for clinical students at various stages. This is because it is at this stage that students are able to pick up good hygiene practices for effective prevention of noscomial infections. However, different barriers have been known to hinder the practice of infection control among these students, hence the need to study such barrier with the aim of finding solutions to them. A descriptive cross-sectional study design was utilized for this study. A total of 239 clinical students participated in the study. Simple random sampling technique was used to select eligible participants. An interviewer-administered structured questionnaire was used to collect relevant information from the participants. The greatest proportions of the respondents, 91.6%, have adequate knowledge about infection control. However, a large proportion of them, 43.4%, have low compliance to infection control measures. More so, respondents identified unavailability of gloves, 88.9%, non-availability of colour codes for waste disposals, 73.2%, lack of time, 75.3%, tasking nature of hand washing, 76.2%, as major barriers to effective infection control practices. Infection control is an integral aspect of practice of any clinical oriented profession. It is therefore imperative that students training to become future health care professionals, be knowledgeable about proper infection control principles, in order to be able to reduce the burden of infectious diseases in Nigeria. Key Words: Barriers, infection control, Clinical students, healthcare professionals.